The Impact of Mixed Marriage in Civil Law Review - Djaoe, Andi Novita Mudriani; Bolo, Suriani Bt.; Baso, Fatihani (Al-'Adl, 2023)
The article aims to reveal the complexities of mixed marriages between local people and mining workers (immigrants). The research method is a qualitative descriptive study that describes the impact of mixed marriages in mining areas in Southeast Sulawesi. The paper shows that mixed marriages are carried out in series without going through the applicable legal procedures. Mixed marriages are based on several aspects behind the legitimacy of providing a way for men (immigrants) as long as they can fulfil the traditional elements, pay for the customs, and are Muslim. Then mixed marriages took place, and it was their (women's) habit who see that immigrant workers could provide welfare. However, mixed marriage indirectly in civil terms means their marriage cannot be recognized and legalized.